Double-layered intelligent energy management for optimal integration of plug-in electric vehicles into distribution systems. (1st January 2019) - Mehta, R.; Verma, P.; Srinivasan, D.; Yang, Jing
Highlights: Double-layered intelligent energy management approach for optimal PEV integration. PEVs are utilized to provide both real and reactive power support to the grid. First layer involves real power management to minimize the PEV (dis)charging cost. Second layer involves reactive power management to minimize system power losses. Abstract: This paper proposes a double-layered intelligent energy management (DIEM) approach for optimal integration of plug-in electric vehicles (PEVs) into a distribution system. The proposed approach involves two optimization layers for real and reactive power management of PEVs which take place at nodal and system level, respectively. The first optimization layer for real power management is designed from nodal aggregator's perspective and aims to minimize the daily total cost incurred for PEV (dis)charging. The second optimization layer for reactive power management is designed from distribution system operator's perspective where the objective is to minimize the system power loss utilizing the reactive power capacity provided by PEVs. The DIEM approach is implemented for PEV integration in a 33-bus distribution system and its performance is assessed against a single-layered intelligent energy management (SIEM) approach which involves only first optimization layer, i.e. real power management of PEVs. The simulation results indicate that utilizing reactive power services of PEVs allows the proposed approach to provide voltage regulation and hence the ability to integrate higher PEV penetration within permissible voltage limits. Furthermore, the simulation results clearly demonstrate the effectiveness and superiority of the proposed DIEM approach in comparison to the SIEM approach.